Oroides pakaluki new genus and new species of Coccidulini from New Guinea (Coleoptera: Coccinellidae) - Tomaszewska, Wioletta; Ślipiński, Adam (Zootaxa, 2012)
Oroides gen. nov., along with O. pakaluki sp. nov. (Coleoptera: Coccinellidae, Coccidulini) from New Guinea is described and illustrated. Placement of this genus within Coccinellidae is discussed.